Production of genetically and developmentally modified seaweeds: exploiting the potential of artificial selection techniques - Charrier, Bénédicte; Rolland, Elodie; Gupta, Vishal; Reddy, C. R. K. (Frontiers in Plant Science, 2015)
Plant feedstock with specific, modified developmental features has been a quest for centuries. Since the development and spread of agriculture, there has been a desire for plants producing disproportionate — or more abundant and more nutritional — biomass that meet human needs better than their native counterparts. Seaweed aquaculture, targeted for human consumption and the production of various raw materials, is a rapidly expanding field and its stakeholders have increasing vested interest for cost-effective and lucrative seaweed cultivation processes. Thus, scientific research on seaweed development is particularly timely: the potential for expansion of seaweed cultivation depends on the sector’s capacity to produce seaweeds with modified morphological features (e.g. thicker blades), higher growth rates or delayed (or even no) fertility. Here, we review the various technical approaches used to modify development in macroalgae, which have attracted little attention from developmental biologists to date. Because seaweed (or marine macroalgae) anatomy is much less complex than that of land plants and because seaweeds belong to three different eukaryotic phyla, the mechanisms controlling their morphogenesis are key to understanding their development. Here, we present efficient sources of developmentally and genetically modified seaweeds — somatic variants, artificial hybrids and mutants — as well as the future potential of these techniques.